Manusia dalam alqur’an : al-basyar, al-ins, al-insan - Ahmad Farid; Nina Ludiana; Putri Balahaqis Eliqa (JURNAL ILMIAH RESEARCH STUDENT, 2023)
The Qur'an describes humans using various terms, including "al-basyar", "al-ins", and "al-insan". "Al-basyar" is typically used to depict humans from a physical and biological perspective. It indicates that humans are creatures created from simple and humble materials, such as dust or soil, and emphasizes the vulnerability and limitations of humans as created beings. "Al-ins" refers to humans in a broader sense, encompassing physical, mental, and spiritual aspects. It affirms that humans are complex creatures with various dimensions and potentials. "Al-insan" is used to portray humans in a context that emphasizes their spiritual and moral potential. It shows that humans have the ability to transcend their physical and biological boundaries and achieve a higher level of existence through good and just behavior. Therefore, the Qur'an provides a very diverse and rich description of humans, including their physical, mental, and spiritual aspects. It shows that humans are very special and valuable creatures in the view of Islam.